Report on research, innovation and technological performance in Germany 2015 - EFI - Commission of Experts for Research; Innovation (Commission of Experts for Research and Innovation (EFI), 2015)
There is little controversy in public debate about the importance of research, innovation and science for employment and prosperity. However, the cause-and-effect relationships are complex, and there is generally a time lag before the results of research and innovation policy can be measured. This makes it all the more important to keep looking at the concrete challenges of research and innovation policy and their long-term implications – even when other tasks seem more urgent in the short term. As in previous years, the 2015 Report of the Commission of Experts for Research and Innovation is divided into three parts. The A chapters discuss topical issues of R&I policy. Focused analyses are presented in the B chapters. And in the C section, the Report documents the development and status quo in Germany by international comparison using eight particularly relevant groups of indicators...
Keywords: 330